The Department of Defense Birth and Infant Health Research Program: Assessing the Reproductive Health of U.S. Active-Duty Women - Khodr, Zeina G.; Bukowinski, Anna T.; Hall, Clinton; Gumbs, Gia R.; Wells, Natalie Y.; Conlin, Ava Marie S. (Seminars in Reproductive Medicine, 2018)
As the percentage of women serving in the active-duty military continues to grow, and as their roles continue to expand, the importance of monitoring reproductive health in the military community increases. The Department of Defense Birth and Infant Health Research (BIHR) program conducts ongoing epidemiologic studies to assess potential increased risks for adverse reproductive and infant health outcomes in the military population. Military personnel endure unique physical and mental demands as a part of their occupational duties (e.g., extensive preventive care, numerous trainings, and deployments), which require special consideration as parental exposures in reproductive health research that cannot be well assessed in the general population. From 2003 to 2014, the BIHR program captured 250,604 pregnancies among approximately 2.4 million active-duty women of reproductive age when limited to non-cadet Army, Air Force, Navy, and Marine Corps personnel. Approximately 15,000 live births occurred each year, and the live birth rate ranged from 76.9 per 1,000 in 2003 to 71.0 per 1,000 in 2014. Safety of military-unique preventive measures, environmental exposures, and occupational hazards in pregnancy are summarized herein. Reproductive health is important to our service members and their families, and optimizing the health of military families ultimately contributes to force readiness.
Keywords: active-duty military women; military readiness; military deployment; reproductive health; pregnancy